Paralytic Toxins Accumulation and Tissue Expression of alpha-Amylase and Lipase Genes in the Pacific Oyster Crassostrea gigas Fed with the Neurotoxic Dinoflagellate Alexandrium catenella - Rolland, Jean-Luc; Pelletier, Kevin; Masseret, Estelle; Rieuvilleneuve, Fabien; Savar, Veronique; Santini, Adrien; Amzil, Zouher (Marine Drugs, 2012)
The pacific oyster Crassostrea gigas was experimentally exposed to the neurotoxic Alexandrium catenella and a non-producer of PSTs, Alexandrium tamarense (control algae), at concentrations corresponding to those observed during the blooming period. At fixed time intervals, from 0 to 48 h, we determined the clearance rate, the total filtered cells, the composition of the fecal ribbons, the profile of the PSP toxins and the variation of the expression of two a-amylase and triacylglecerol lipase precursor (TLP) genes through semi-quantitative RT-PCR. The results showed a significant decrease of the clearance rate of C. gigas fed with both Alexandrium species. However, from 29 to 48 h, the clearance rate and cell filtration activity increased only in oysters fed with A. tamarense. The toxin concentrations in the digestive gland rose above the sanitary threshold in less than 48 h of exposure and GTX6, a compound absent in A. catenella cells, accumulated. The a-amylase B gene expression level increased significantly in the time interval from 6 to 48 h in the digestive gland of oysters fed with A. tamarense, whereas the TLP gene transcript was significantly up-regulated in the digestive gland of oysters fed with the neurotoxic A. catenella. All together, these results suggest that the digestion capacity could be affected by PSP toxins.